Oracle FAQ Your Portal to the Oracle Knowledge Grid
HOME | ASK QUESTION | ADD INFO | SEARCH | E-MAIL US
 

Home -> Community -> Usenet -> comp.databases.theory -> armstrong's axioms: augmentation - help pls

armstrong's axioms: augmentation - help pls

From: loveboat <l0veb0at_at_gmx.de>
Date: Thu, 2 Dec 2004 13:05:09 +0100
Message-ID: <con0pi$c5c$1@svr7.m-online.net>


hi,

in armstrongs axioms, i don't get the augmentation, which is: (X -> Y) => (XZ -> YZ)

why is that? i mean when Y is functional depending from X, i can't just add another set of attributes and make them dependent as well? (at least that's what i think)
why can i do that?
thx for help,
toni Received on Thu Dec 02 2004 - 06:05:09 CST

Original text of this message

HOME | ASK QUESTION | ADD INFO | SEARCH | E-MAIL US